Research on Primary Frequency Modulation of Coordinated Control System for Wind Power Generator and Thermal Power Unit. Issue 1 (May 2020) - Han, Yingkun; Gao, Song; Li, Lei; Miao, Weiwei; Li, Yuanyuan; Yan, Qing
Abstract: Combined with the practical problems in the development of power system, the paper introduces the technical scheme and characteristics of primary frequency modulation(PFM) for thermal power units. Aiming at the impact of the rapid development of wind power generation on the stable operation of the power grid, the PFM strategy on the coordinated control system for wind power generators and thermal power units is proposed to dynamically adjust the PFM capacity of thermal power units, which effectively make up for the adverse impact of the uncertainty of wind power generation, and improve the stable operation capacity of the power grid. It has certain reference significance on the flexible operation control optimization of the power grid in the wind power centralized area.